Physics Versus Geophysics - Ivanchin A. Alexander (Saarbruecken, LAP Lambert Academic Publishing, 2015)
Morden geophysics seems to ignore the general laws of physics and mathematics. For instance, when the currents in the lithosphere and in the ocean are considered, the mechanics of continua and the elasticity theory are not even mentioned. In the "theories" of the drift of tectonic plates and the formation of volcanoes running counter to the seismology data on the origin of transverse waves the mantle is treated as a liquid. It is stated that the whirling currents in the atmosphere and oceans are caused by the drops in temperature, pressure, salinity, etc, that is by thermodynamic potential forces, which in accordance with the laws of mathematics cannot, in principle, produce moments of force, that is vortices. The existence of the continents and their motion is accounted for by the jet stream in the mantle, whose speeds according to the simplest estimates, must be hundreds of meters per second. In this monograph a critical discussion of the existing geophysical hypotheses is presented. Also, physical theories of earthquakes, volcanoes, lithosphere stresses, oceanic currents and tornadoes are put forward.